The Nearsightedness of the IMF - (:unkn) unknown (My University, 2003)
Africa is the poorest continent in the world. The great hopes from independence were not implemented. The goals of IMF and World Bank are promoting cooperation and financing economic development. With the Washington consensus, they encouraged the emergence of a rich minority at the expense of the poor majority. Then, the development of Africa was a failure, with a lot of corruption. Africa was very badly advised. However, since ten years, IMF lunch some specific actions for fighting against endemic poverty, economic development cannot be exclusively managed from « the top ». A new strategy must be built, with less private aid, the development of good public governance respecting human rights and a more transparent policy for the foreign investors. IMF had failed in its mission. It must do something to repair it, such as a new Marshall Plan, in order to give Africa the possibility if its development, such as a new Marshall Plan, in order to give Africa the possibility if its development.
Keywords: African Research